The study of the completeness of the removal of the detergents from children's clothes by the amount of anionic surfactants in wastewater (Environment & Health, 2021)
Objective: We determined a safety level of the agents by the residual amount of the anionic surfactants in wastewater from the objects after their washing with the agents for the treatment of children's products.Materials and methods: 16 detergents for children's clothes washing were purchased at the supermarkets of Kyiv. In our study we applied sanitary-and-chemical research methods: express method for the assessment of the anionic surfactants on the clothes fabrics; an extraction-photometric method for the determination of the the residual amount of the main active substances of the anionic surfactants in the experimental sample.Results: The analysis of the results shows that there is a significant difference in the surfactant amount in the wastewater after washing with powder and liquid detergents based on the synthetic anionic surfactants and natural soap. Therefore, the anionic surfactants are rinsing best of all from the clothes washed with the detergents based on natural soaps (Soaps “Droog”, “Clean & White”, “Kroha”). After washing of the children's clothes with powder and liquid detergents for automatic washing based on synthetic anionic surfactants, the residual amount of the anionic surfactants on the fabrics exceeds the accepted hygienic standard.Conclusions: It has been discovered that even after repeated rinsing, the fabrics, treated with washing powder and liquid detergents, contain the residual amount of the anionic surfactants that exceeds normative parameters (8 of 13 investigated detergents based on the anionic surfactants) by 2-3 times.Taking into account a specificity of children’s functional skin state, especially the incompletely formed multistage protection system, it is recommended to use the detergents based on natural soap and products containing less than 5% of the surfactants for washing of the clothes of the children aged 0 to 6 years.
Keywords: detergents for washing of children's clothes; anionic surfactant residual amount; surfactants